A glassy carbon electrode modified with graphene oxide and silver nanoparticles for amperometric determination of hydrogen peroxide - An'Amt bin Mohamed Noor; Muhammad Mehmood Shahid; Perumal Rameshkumar; Nay Ming Huang
The article describes a glassy carbon electrode (GCE) modified with a nanocomposite consisting of graphene oxide and silver nanoparticles, and its application to amperometric determination of hydrogen peroxide (H2O2). Cyclic voltammetry with this modified electrode reveals efficient electrocatalytic reduction of H2O2. The response to H2O2 at a working potential of −0.3 V (vs. Ag/AgCl) is linear in the 100 μM to 11 mM concentration range at pH 7.2. The limit of detection is 28.3 μM (at an S/N ratio of 3). Good selectivity is observed over physiological interferents such as dopamine, ascorbic acid, uric acid and glucose. © 2015, Springer-Verlag Wien.